Integrated traditional Chinese and western medicine nursing based on integration of medical care for pain management in a patient with diabetic foot disease complicated with erysipelas (医护一体化模式下1例糖尿病足合并丹毒患者的中西医结合疼痛护理体会) - ZHI Hui (智慧); ZHENG Wen (郑雯); ZHENG Jiaqi (郑佳琪); LIU Jinjing (刘津京) (Association of Integrative Nursing, 2023)
This paper summarized the integrated traditional Chinese and western medicine nursing based on integration of medical care for pain management in a patient with diabetic foot disease complicated with erysipelas. An integration team of medical care specialists was established for consultation instruction, evaluation, diagnosis, treatment and nursing. Based on the syndrome differentiation, integrative nursing measures included Chinese herbal medicine application, Traditional Chinese Medicine collapse stains, acupuncture and health education before discharge from hospital were carried out to relieve the pain and improve the quality of life of the patient. (本文总结医护一体化模式下1例糖尿病足合并丹毒患者的中西医结合疼痛护理经验。组建医护一体化小组, 医护相互协作, 根据医生的中医辨证, 从专科方面进行指导, 制订中西医结合护理措施, 开展中药贴敷、中药塌渍、针刺治疗、出院指导等全方面、整体连续性的护理措施, 有效减轻患者疼痛, 提高生活质量。)